Geographical Integration and the Retail CD-Pricing Decisions of Large Depository Institutions - Cooperman, Elizabeth S.; Lee, Winson B.; Lesage, James. P. (The Review of Economics and Statistics, 1991)
Elizabeth S. Cooperman, Winson B. Lee, James. P. Lesage, Geographical Integration and the Retail CD-Pricing Decisions of Large Depository Institutions, The Review of Economics and Statistics, Vol. 73, No. 3 (Aug., 1991), pp. 546-552